Design and Optimization of Renewable Energy Sources for Low Voltage Hybrid Microgrid System (HMGS) - R. Sai Kiran, S. Suresh Reddy (International Journal of Advanced Science and Technology, 2021)
Hybrid microgrid systems (HMGS) comprise of several parallel connected distributed resources with electronically controlled strategies, which are capable to operate in both islanded and grid connected mode. HMGS based on renewable energy sources (RES) is the cost-effective option for solving the power supply problem in remote areas, which are located far from grids. In this paper, the wind and solar meteorological data are used to design Islanded HMGS for providing necessary electricity. Cost effectiveness and system reliability are major factors considered for designing HMGS to achieve better power management scheme. Particle Swarm Optimization (PSO) scheme is applied to identify the sizing of wind turbines (WT), photovoltaic (PV) module, battery energy storage system (BESS) and diesel generator, and find the optimal configuration of HMGS system. The design and optimal operation of HMGS system has been developed and validated through MATLAB software.